Evaluating the energy efficiency of rolling stock power units - Kochergin Victor; Abramov Andrey; Zinchenko Evgeniy (E3S Web of Conferences, 2023)
The paper describes the main methods of ensuring the energy efficiency of rolling stock, and justifies the main generalised functional quality indicators of control systems. There is a description of possible approaches to a comparative assessment of the feasibility of choosing a control method. A proposal to use a generalized target functional for minimizing the cost components of the control processes has been made. The results of the research make it possible to state that economic feasibility and minimisation of labour and material costs for control are the mandatory requirement when choosing methods of controlling the energy efficiency of rolling stock. It is shown that the control of parameters necessary for accounting and planning can be ineffective because of the high cost of acquisition and maintenance of control tools. Expressions for determining the components of the total cost of control are presented. In general terms they consist of the cost of control, the cost of measurement errors and the cost of machine downtime during control. A control system based on an algorithm for measuring fuel consumption by measuring the electrical power of a diesel generator has been developed. The replacement of average normative values of fuel consumption by actual values of total and specific fuel consumption makes it possible to increase the objectivity of rolling stock energy efficiency control.